1980
DOI: 10.1099/00221287-120-2-369
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron Microscopic Study of the Location of Group-specific and Type-specific Polysaccharide Antigens on Isolated Walls of Group B Streptococci

Abstract: The ultrastructural locations of the group-specific polysaccharide and the type-specific polysaccharides Ia, Ib, II and III of group B streptococci (Streptococcus agalactiae) were studied on isolated walls by the direct immunoferritin technique. The type polysaccharides were located exclusively on the outer side of the wall on which they formed a distinct capsule. Except for strain 58/59 (type Ia) the thickness of the capsule was characteristic of each strain investigated. In all strains the type-specific ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

1982
1982
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…Ultrastructural studies have demonstrated that some GBS strains show a remarkable variation in the size of the enveloping polysaccharide capsule (16). This finding agrees with the present results showing that an apparently homogeneous strain may contain subpopulations of bacteria with different buoyant densities.…”
Section: Discussionsupporting
confidence: 93%
“…Ultrastructural studies have demonstrated that some GBS strains show a remarkable variation in the size of the enveloping polysaccharide capsule (16). This finding agrees with the present results showing that an apparently homogeneous strain may contain subpopulations of bacteria with different buoyant densities.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, labelling with conjugated specific antibodies shows that the envelope incorporates and transports antigens belonging to the extemal layers of the ce11 wall. This observation has also been made on Gram-positive (Swanson et al 1969;Chem Lai et al 1973;Wagner et al 1980) and Gram-negative bacteria (Bayer and Thurow 1977).…”
Section: Resultssupporting
confidence: 50%
“…The ultrastructure of streptococci such as S. pneumoniae (36, 37), S. mutans (29), and group B streptococci (20,26,33,39) has been examined. Surface fibrils or fimbriae were observed on different strains of S. salivarius (13), S. sanguis (14), S. mitior (12), and Enterococcus faecalis (15).…”
mentioning
confidence: 99%